Storage conditions, energy consumption, and food safety implications of domestic refrigerators in Bangkok - Chaomuang, Nattawut; Potisuwan, Cheeraphat; Duret, Steven; Derens-Bertheau, Evelyne; Paviet-Salomon, Yvanne; Nukunudompanich, Methawee; Laguerre, Onrawee (My University, 2025)
Domestic refrigeration plays a critical role in food preservation and safety by maintaining optimal storage conditions for perishable items. This study investigated the temperature and humidity conditions, as well as the energy consumption, of domestic refrigerators in Bangkok. Data were collected through on-site investigations of 123 refrigerators using data loggers to record temperature, humidity, and electrical consumption over a five-day period. In addition, a predictive microbiological model was used to assess the potential for microbial growth under the investigated storage conditions, specifically of Listeria monocytogenes and lactic acid bacteria (LAB). Results indicated that although the overall mean temperatures of chilling compartments (5.0 ± 2.5 °C) were within the recommended range for domestic refrigeration, only about 30–40 % of individual refrigerators consistently maintained temperatures at or below 5 °C on the top and middle shelves throughout the five-day monitoring period, where fresh and ready-to-eat products are typically stored. Electrical consumption analysis revealed significant differences across refrigerator types; appliances with two doors and bottom freezers exhibited the highest annual electrical consumption, while single door refrigerators recorded the lowest. However, the specific energy consumption (SEC) did not differ significantly among refrigerator types. The microbial exposure assessment based on a test product highlighted that for over 50 % of refrigerators, L. monocytogenes load exceeds the regulation safety limits (> 102 CFU/g) within five days. These findings emphasize the need for improved temperature control, appliance design, and consumer education to ensure food safety and energy efficiency in domestic refrigeration.
Keywords: Cold chain; Food preservation; Food safety; Freezer; Fridge; Predictive microbiology; Temperature control